Calculated compassion in Emirati higher education: psychopathy’s ethical rhetoric during crises - Alowais, Abdelaziz Abdalla; Suliman, Abubakr (Frontiers in Education, 2025)
IntroductionCrises in higher education institutions (HEIs) often demand authentic care, responsibility, and ethical leadership. However, leaders with psychopathic traits–such as superficial charm, manipulativeness, and a lack of empathy–may strategically deploy ethical rhetoric to protect their self-interest. In the context of Emirati HEIs, where hierarchical norms and institutional prestige shape leader-follower dynamics, this “calculated compassion” can mask harmful decision-making and undermine organizational well-being.MethodsThis qualitative study drew on semi-structured interviews with 18 employees working across public and private HEIs in the United Arab Emirates. Interviews explored participants’ experiences with leadership behavior during institutional crises, such as layoffs, program closures, and organizational restructuring. Data were analyzed using reflexive thematic analysis to identify recurring patterns of crisis-time manipulation embedded within ethical discourse.ResultsThree major themes emerged. (1) Moral Theatre: Staged Compassion During Layoffs and Closures—leaders publicly enacted empathy and ethical concern while privately endorsing decisions that intensified employee vulnerability. (2) Strategic Sympathy: Selective Use of Ethics to Shield Reputations—ethical language was mobilized defensively to maintain institutional legitimacy and leader image, particularly during contentious decisions. (3) Aftershocks of Betrayal: Trust Erosion and Long-Term Disengagement–employees described profound disillusionment, leading to reduced morale, diminished organizational commitment, and persistent relational distrust.DiscussionFindings demonstrate that psychopathic traits enable leaders to transform ethical rhetoric into a tool of manipulation during crises. This “calculated compassion” produces a deceptive moral façade that obscures self-serving decision-making and harms employee trust. By highlighting how crisis-time ethics can be strategically weaponized, the study extends leadership ethics and crisis management scholarship and contributes a regional perspective on the hidden costs of destructive leadership in HEIs operating under global and national policy pressures.